A case study for optimising the geometry and moment capacity of code compliant welded RWS connections - Bayat, Meysam; Tsavdaridis, Konstantinos Daniel; Alonso-Rodriguez, Andrés (Frontiers in Built Environment, 2025)
A sustainable and resilient built environment requires structural solutions that minimise the use of high-environmental impact materials, while ensuring sound structural behaviour to extreme events. This study presents a seismic retrofit strategy employing reduced web section (RWS) connections to ensure inelastic behaviour initiates into the beam web within a designated protected zone, effectively protecting joints from stress concentration, while optimising the use of structural steel. RWS connections maintain flange integrity, allowing larger moment capacities to those cutting flanges while limiting out-of-plane instability to a greater extent. This method also allows for retrofitting from the level below, avoiding floor demolition. However, improper positioning or sizing of the web opening can lead to a non-compliant RWS connection compromising the capacity to withstand drift demands and altering the connection classification from fully restrained to partially restrained. To address these fine issues, this paper studies detailed finite element models aimed at optimising welded RWS connection designs subjected to AISC 341 loading protocol, while focusing on beam-column interface spacing and perforation diameter. This improves the state of the art by extending knowledge from bolted RWS to their welded counterparts, employing capacity design principles. Moreover, current literature lacks definitive guidance on optimal knowledge and diameter ranges for RWS connections. This study addresses this gap by performing a parametric analysis of ninety finite element models with fixed boundary conditions in ABAQUS to identify the optimal geometrical parameters for Circular-cut RWS connections using IPE270 beams. The results show that specimens within the proposed range achieved ultimate drift demands over 4%, meeting AISC criteria for special moment frames with less than 20% strength degradation. The findings highlight that RWS connections are plausible solutions for seismic retrofit low-rise dwellings.